Minimum Wages and the Uptake of Supplemental Security Income - Krishna Regmi (Institute of Labor Economics (IZA), 2024)
This study investigates whether the minimum wage affects the uptake of Supplemental Security Income (SSI). To disentangle the effect of the minimum wage from underlying macroeconomic conditions, I use a triple-differences-type model that exploits cross-state and temporal differences in the minimum wage and its differential effects on those individuals with and without a high school diploma. The results show that a one percent increase in the minimum wage leads to a 0.33 percent decline in SSI uptake. To substantiate the findings, this study employs an alternative approach, leveraging the discontinuity in minimum wage legislation at state borders by comparing SSI uptake within the contiguous state-border counties. Using this approach yields qualitatively similar findings, corroborating the baseline estimates.
Keywords: J08; 330; minimum wage; Supplemental Security Income; border discontinuity; means-tested programs